2020
DOI: 10.1016/j.childyouth.2020.105658
|View full text |Cite
|
Sign up to set email alerts
|

Mental health outcomes during the COVID-19 and perceptions towards the pandemic: Findings from a cross sectional study among Bangladeshi students

Abstract: Highlights This is the first few studies exploring the perceptions of Bangladeshi students towards the COVID-19 pandemic. Female students showed higher stress levels, greater anxiety symptoms and, depressive symptoms. Younger students had a greater psychological impact due to COVID-19 than senior students. The psychological impact is higher among those students who have at least one COVID-19 like symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
1
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(116 citation statements)
references
References 25 publications
9
97
1
9
Order By: Relevance
“…A total of 7 cross-sectional online survey-based studies were included in this review after adhering to the inclusion criteria. 31–37 All of the studies were conducted between April and May 2020. The number of participants ranged from 425 to 15,543; whereas only 3 studies reported participant mean age.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 7 cross-sectional online survey-based studies were included in this review after adhering to the inclusion criteria. 31–37 All of the studies were conducted between April and May 2020. The number of participants ranged from 425 to 15,543; whereas only 3 studies reported participant mean age.…”
Section: Resultsmentioning
confidence: 99%
“… 32 Also, a 61.9% prevalence rate of depression was identified in a study, although detail about the student status was not mentioned in that study. 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with mild to severe levels of negative domains of mental health were considered positive to a mental health disorder, otherwise treated as no depressive symptoms, anxiety symptoms, and stress level. The DASS-21 has proven to be reliable and relevant for assessing mental health in the Bangladeshi population ( Alim et al, 2015 ; Banna et al, 2020 ; Sadiq et al, 2019 ; Sayeed et al, 2020b , 2020a ). The Cronbach's alpha coefficient of the DASS-21 was 0.92, indicating acceptable internal consistency ( Taber, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sintomas relacionados à depressão, ansiedade, preocupação, estresse e solidão durante a pandemia da COVID-19 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i4.14125 foram evidenciados por Pan et al (2020) e Sayeed et al (2020) com holandeses e universitários de Bangladesh, respectivamente. Vale destacar que o estado de saúde mental pode influenciar diretamente na alimentação, pois de acordo com Mantau et al (2018), pessoas tendem a regular o humor negativo por meio do consumo de alimentos não saudáveis, fenômeno chamado de "alimentação emocional".…”
Section: Introductionunclassified